2022
DOI: 10.1039/d2se00384h
|View full text |Cite
|
Sign up to set email alerts
|

Defect passivation in perovskite solar cells using an amino-functionalized BODIPY fluorophore

Abstract: The presence of defects formed during the growth and crystallization of perovskite films is a limiting factor to achieve high efficiency and stability in perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The diffraction peaks of the photoactive phase (α-phase), non-perovskite phase (δ-phase), and PbI 2− x Br x in the films were visible at 14.2, 11.7, and 12.8°, respectively. 34,69 We note that the diffraction peak corresponding to PbI 2− x Br x disappeared for the MWA–TOPO film, indicating that the formation of the Pb clusters known for defect sites was completely suppressed. 59 This is attributed to the establishment of a Pb–O bond by the coordination of TOPO to Pb 2+ ions both in the bulk and at the surface.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The diffraction peaks of the photoactive phase (α-phase), non-perovskite phase (δ-phase), and PbI 2− x Br x in the films were visible at 14.2, 11.7, and 12.8°, respectively. 34,69 We note that the diffraction peak corresponding to PbI 2− x Br x disappeared for the MWA–TOPO film, indicating that the formation of the Pb clusters known for defect sites was completely suppressed. 59 This is attributed to the establishment of a Pb–O bond by the coordination of TOPO to Pb 2+ ions both in the bulk and at the surface.…”
Section: Resultsmentioning
confidence: 88%
“…30–32 This post-treatment method reduces surface defects. 33–40 However, bulk defects are unlikely to be passivated because the low diffusivity and the compact film morphology handicap diffusion into the bulk of perovskite films. A few studies have reported the passivation of bulk defects using TOPO via addition into perovskite solutions or dripping a TOPO solution into a perovskite antisolvent during spin coating.…”
Section: Introductionmentioning
confidence: 99%
“…The pristine perovskite consists of two Pb 4f binding energy peaks situated at 142.60 and 137.75 eV corresponding to the Pb 4f 5/2 and Pb 4f 7/2 levels respectively, and both peaks undergo an ∼0.2 eV shift toward lower-binding-energy positions after the incorporation of allantoin. This binding energy shift can be due to the increase in the electron cloud density near Pb 2+ after the donation of lone pair electrons in the carbonyl group in the allantoin to form the coordination bond. ,, In the case of iodine, XPS measurement failed to observe any shift for 3d orbitals. This could be due to the considerably weaker interaction between iodine and allantoin.…”
Section: Resultsmentioning
confidence: 99%
“…Upon verifying their successful exfoliation in 2D forms, the BiTeI flakes were then incorporated as functional additives into the perovskite layer, aiming at tuning the overall carrier concentration and charge transporting properties at the interfaces of perovskite with the charge transporting layers. It is noteworthy that the I-terminated surfaces of the BiTeI flakes could promote the interaction with the undercoordinated Pb atoms of the perovskite, 84 reducing the trap density of the absorber layer. Thus, the BiTeI flakes were mixed in the perovskite precursor solution, varying their concentration between 0.008 mg mL −1 and 0.1 mg mL −1 .…”
Section: Resultsmentioning
confidence: 99%